Modeling of CPW Based Passive Networks using Sonnet Simulations for High Efficiency Power Amplifier MMIC Design - Zomorrodian, Valiallah; Mishra, U. K.; York, Robert A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper, the capabilities of the Sonnet software for accurate modeling and design of CPW based lumped-element resonators and matching networks is studied. A systematic method for design of complex matching networks using Sonnet is presented and good overall agreement between Sonnet simulations and measured s-parameter data from fabricated resonators and matching networks was obtained.